Pengaruh Strategi Promosi terhadap Keputusan Pembelian pada Toko Freedom Street Wear di Shopee - Intan Ullyatul Fasyah; Santoso Santoso; Arida Murti Martikasari (Journal Economic Excellence Ibnu Sina, 2025)
This study aims to analyze the effect of promotional strategies on consumer purchasing decisions for Freedom Street Wear products on the Shopee platform. The research population consists of Shopee users who have purchased products from official stores. A quantitative approach using a survey method was applied, and data was collected from 100 respondents selected through non-probability sampling. Multiple linear regression analysis was used to test the influence of each variable, both partially and simultaneously. The findings show that Double Date Discount has a positive and significant effect on purchasing decisions. Meanwhile, Free Shipping and Cash on Delivery (COD) did not have a significant effect, although COD showed a positive trend. Simultaneously, these three variables were found to have a significant effect on consumer purchasing decisions. In addition to examining the individual effects of promotional strategies, this study also explored the interactive relationships between the variables. It was found that while Free Shipping and COD did not individually influence purchasing decisions, their combination with other promotional strategies like Double Date Discount enhanced the overall effectiveness of the promotions. This suggests that promotional strategies should be strategically integrated to maximize their impact on consumer behavior. Furthermore, the study highlights the growing importance of e-commerce platforms like Shopee in influencing purchasing decisions and shaping consumer perceptions. As online shopping continues to grow, understanding the nuances of promotional strategies is essential for businesses aiming to attract and retain customers in a competitive market. The findings contribute to a deeper understanding of the factors driving consumer purchasing decisions and offer valuable insights for businesses looking to optimize their promotional efforts in the online retail environment.